The Integrated Physics Learning E-Module with Pancasila Character Values in Work and Energy Subjects as Solution to Improve Students’ Critical Thinking Ability and Independence: Is It Effective? - Sari, Aprilia Mayang; Ariswan, Ariswan (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
One of the learning resources chosen to solve problems related to the low critical thinking ability and students' independence is modules. This research aims to reveal the effectiveness of an integrated physics learning e-module with Pancasila character values in work and energy subjects to improve students' critical thinking ability and independence. This research used a pre-experimental design with a pretest-post-test control group design. This design involved a total of 70 students from class X MIPA at SMA N 1 Kasihan with an average age of 15-16 years old. These research subjects were selected using a cluster sampling technique. Data collection techniques in this study were used to test techniques, namely the critical thinking ability test and questionnaire techniques. The data collection instrument used a test instrument for essential thinking ability and student independence questionnaires. The data analysis technique used was the n-gain analysis, Multivariate Analysis of Variance (MANOVA) test, and effect size analysis by calculating the value of Cohen's f. This research indicates that the integrated physics learning e-module with Pancasila character values in work and energy subjects effectively improves students' critical thinking ability and independence.